Development of osteomyelitis following dental abscesses: influence of therapy and comorbidities - Moratin, Julius; Freudlsperger, Christian; Semmelmayer, Karl; Braß, Caroline; Berger, Moritz; Engel, Michael; Hoffmann, Jürgen; Ristow, Oliver (Clinical oral investigations, 2021)
Bacterial osteomyelitis of the jaw is a severe disease potentially requiring extensive surgical treatment. We have evaluated the incidence rates of bacterial osteomyelitis following dental abscessation associated with primary or secondary tooth extraction.
Published: 07 July 2020
Gesehen am 13.09.2021